Bifurcation behaviour and limit cycles of a compliant seal‐rotor system. Issue 1 (October 2016) - Baeuerle, Simon; Hetzler, Hartmut
Abstract: This contribution discusses the non‐linear dynamic behaviour of a rotor system equipped with a compliant seal. The investigated model consists of a Laval ‐Rotor and a stiff seal ring which is visco‐elastically supported. The fluid forces stemming from the turbulent incompressible lubricant film are accounted for by the non‐linear Muszynska model. The added compliance leads to an improved stability behaviour of the steady state. Within the post‐critical regime the additional compliance gives rise to bifurcations of the stationary vibration: Hopf bifurcations lead to limit cycles which can loose their stability via Neimark‐Sacker bifurcations. (© 2016 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)